APPLICATION OF ANALYTICAL TOOLS IN THE CONSERVATION OF THE AFRICAN ELEPHANT (LOXODONTA AFRICANA) - S. Mashele (Journal of Animal and Plant Sciences, 2011)
There is a great need to characterize African elephant ivory for controlling poaching and implementation of national and international laws. In this study, Ivory samples (117) from South African and Namibian sources were analysed for elemental presence using UV laser magnetic sector inductively coupled plasma-mass spectroscopy (ICP-MS). A total of forty five elements were detected. The analysis of variance was carried out over 13 regions. The concentration of elements showed statistically significant differences (p< 0.0001) between ivory obtained from different regions. The discriminant analysis was employed to determine whether the existing data can be correctly classified into their region of origin. The data suggested that various elements from distinct ecological regions can present in different concentrations. The relationship of these elements may lead to the establishment of characteristic elemental patterns, unique for each ivory source. This study indicates that chemical analysis of ivory could be beneficial in tracing the source of illegal ivory. This knowledge may play a role in the conservation of the elephant herds.
Keywords: Elephant ivory; composition; Environment; laser ablation ICP-MS